If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 12 = -18 + 6x Reorder the terms: 12 + 4x = -18 + 6x Solving 12 + 4x = -18 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12 + 4x + -6x = -18 + 6x + -6x Combine like terms: 4x + -6x = -2x 12 + -2x = -18 + 6x + -6x Combine like terms: 6x + -6x = 0 12 + -2x = -18 + 0 12 + -2x = -18 Add '-12' to each side of the equation. 12 + -12 + -2x = -18 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = -18 + -12 -2x = -18 + -12 Combine like terms: -18 + -12 = -30 -2x = -30 Divide each side by '-2'. x = 15 Simplifying x = 15
| 1/2(x+10)=1/3(x+9) | | 17-6n=44+10n | | 0.2-(0.5-x)=-0.1 | | y-2=x-3 | | -4(-5m-9)=-17m+12 | | .3333+11=.5-3 | | 2x+80+x/2=1 | | 4x-12+2x+3=x | | (2/3)*(3/7) | | 7(-3+1)-(1+5-3)=0 | | (5a+10)=(3a+10) | | -7(1+3r)+3r=3-8r | | u=3(8n+34)+7(n+1) | | 2x+80+x/2=120 | | 54=.5(12h) | | (2x+5)/4=x/3 | | (-3/7)*(-7/3) | | 12-10x+5x=18 | | -8-v=-1 | | -1/7(7y+4) | | (-9)+(-2)= | | -3(b+5)=-6 | | 2*(1/2) | | (3x)=(5x-48) | | 100*3.14=2*3.14r | | 36/x=18 | | g-(-16)=44 | | (10/11)*(-7/5) | | 10+14w=2(-3w-13) | | P+5=p | | x+14-7=12 | | (-5)+7= |